Microbial metabolism of transparent exopolymer particles during the summer months along a eutrophic estuary system - Bar-Zeev, Edo; Rahav, Eyal (Frontiers in Microbiology, 2015)
This study explores the role of transparent exopolymer particles (TEP) as an additional carbon source for heterotrophic microbial activity in the eutrophic Qishon estuary. From the coastal station and upstream the estuary; TEP concentrations, β-glucosidase activity, bacterial production and abundance have gradually increased. TEP were often found as bio-aggregates, scaffolding algae, detritus matter and bacteria that likely formed “hotspots” for enhance microbial activity. To further demonstrate the link between TEP and heterotrophic bacterial activity, confined incubations with ambient and polysaccharide-enriched estuary water were carried out. Following polysaccharide addition, elevated (~50%) β-glucosidase activity rates were observed, leading to TEP hydrolysis. This newly formed bioavailable carbon resulted in significantly higher growth rates, with up to a 5-fold increase in heterotrophic bacterial biomass, comprising mostly high nucleic acid content bacteria. Taking together the findings from this research, we conclude that even in highly eutrophic environments heterotrophic bacteria may still be carbon limited. Further, TEP as a polysaccharide matrix can act as a metabolic surrogate, adding fresh bioavailable carbon through tight associations with bacteria in eutrophic ecosystems such as the Qishon estuary.